Impact of the preoperative skeletal muscle index on early remnant liver regeneration in living donors after liver transplantation - Sunyoung Lee; Kyoung Won Kim; Heon-Ju Kwon; Jeongjin Lee; Gi-Won Song; Sung-Gyu Lee (Korean Journal of Transplantation, 2022)
Background : We investigated the correlation between the preoperative skeletal muscle index (SMI) and remnant liver regeneration after right hemihepatectomy for living-donor liver transplantation and aimed to identify preoperative predictors of greater early remnant liver regeneration in living donors. Methods : This retrospective study included 525 right hemiliver donors (mean age, 28.9±8.3 years; 345 male patients) between 2017 and 2018, who underwent computed tomography before surgery and on postoperative day (POD) 7. Preoperative anthropometry, laboratory parameters, skeletal muscle area at the third lumbar vertebral level, and liver volume before and after surgery were evaluated. Correlations were analyzed using Pearson correlation coefficients, and stepwise multiple regression analysis was performed to identify independent predictors of greater remnant liver regeneration. Results : Remnant liver regeneration volume on POD 7 was positively correlated with body mass index (BMI; r=0.280, P<0.001) and SMI (r=0.322, P<0.001), and negatively correlated with age (r=–0.154, P<0.001) and the ratio of future remnant liver volume (FRLV) to total liver volume (TLV; r=–0.261, P<0.001). Stepwise multiple regression analysis showed that high BMI (β=0.146; P=0.001) and SMI (β=0.228, P<0.001), young age (β=–0.091, P=0.025), and a low FRLV/TLV ratio (β=–0.225, P<0.001) were predictors of greater remnant liver regeneration. Conclusions: High SMI and BMI, young age, and a low FRLV/TLV ratio may predict greater early remnant liver regeneration in living donors after LDLT.